2016
DOI: 10.1080/17843286.2016.1200824
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two different exercise programs on chronic fatigue in lupus patients

Abstract: Patients included in the STG and the HTG similarly improved their fatigue, irrespectively of their level of compliance, raising the possibility that the beneficial effect on fatigue was not only exercise-related.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Two RCT of exercise in SLE demonstrated clinically significant reductions in fatigue. Of note, improvement in fatigue (using the FSS) was noted even in patients with low adherence in one of these studies, raising the question of bias in the intervention group 20,21 . Low glycemic index and low-calorie diets were also shown to decrease fatigue in SLE patients when measured by the FSS.…”
Section: Resultsmentioning
confidence: 95%
“…Two RCT of exercise in SLE demonstrated clinically significant reductions in fatigue. Of note, improvement in fatigue (using the FSS) was noted even in patients with low adherence in one of these studies, raising the question of bias in the intervention group 20,21 . Low glycemic index and low-calorie diets were also shown to decrease fatigue in SLE patients when measured by the FSS.…”
Section: Resultsmentioning
confidence: 95%
“…19 Therapeutic exercise also had a benefit in childhood-onset SLE patients (C-SLE). 17,26 In a cross-sectional study (n=242) by Volkmann, et al that assessed the association of physical exercise with certain cardiovascular risk markers did not find any correlation between activity or damage of SLE and exercise. 28 Prado, et al and Reis-Neto, et…”
Section: Therapeutic Exercise In Slementioning
confidence: 96%
“…60 Exercise does not worsen disease activity, 61,62 and has been associated with improvements in fatigue in SLE. 26,5258 This has been shown via controlled trials of aerobic exercise regimens, 52,54,56 as well as a cross-sectional study that compared more physically active SLE patients to controls. 26 As fatigue remains a significant barrier to quality of life in SLE, 59 identifying strategies for improving this is critical.…”
Section: Introductionmentioning
confidence: 94%
“…Several controlled trials have evaluated 12-week aerobic exercise programs, and have shown they improved fatigue, 52,54,56 depression, 52 aerobic capacity, 64 and quality of life. 52,64 Even without targeted exercise training or regular compliance, SLE patients who engaged in more physical activity still felt improvement in fatigue compared to controls.…”
Section: Introductionmentioning
confidence: 99%